2015
DOI: 10.1186/1744-8069-11-2
|View full text |Cite
|
Sign up to set email alerts
|

Viral Vectors Encoding Endomorphins and Serine Histogranin Attenuate Neuropathic Pain Symptoms after Spinal Cord Injury in Rats

Abstract: BackgroundThe treatment of spinal cord injury (SCI)-induced neuropathic pain presents a challenging healthcare problem. The lack of available robust pharmacological treatments underscores the need for novel therapeutic methods and approaches. Due to the complex character of neuropathic pain following SCI, therapies targeting multiple mechanisms may be a better choice for obtaining sufficient long-term pain relief. Previous studies in our lab showed analgesic effects using combinations of an NMDA antagonist pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…However, treatments remain limited, and are aimed mainly at supportive care due to the complex character of SCI (Nasirinezhad et al, 2015). Recent findings have indicated that SCI causes profound muscular atrophy, and bone loss with fragility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, treatments remain limited, and are aimed mainly at supportive care due to the complex character of SCI (Nasirinezhad et al, 2015). Recent findings have indicated that SCI causes profound muscular atrophy, and bone loss with fragility.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment is a challenging healthcare problem due to involvement of a complex cascade of secondary neurodegenerative events set in motion by the primary injury, coupled with the lack of available robust pharmacological and novel therapeutic approaches (Nasirinezhad et al, 2015). Glucocorticoid steroids, mainly methylprednisolone (MP), have been extensively used in the clinical treatment of spinal cord trauma beginning in the mid-1960s and throughout the 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…Various classes of drugs with analgesic characteristic are applied for treating neuropathic pain [7]. In addition to drug therapy, non-drug treatments for neuropathic pain such as surgery, acupuncture, transcutaneous electrical nerve stimulation, psychotherapy, and physiotherapy exist [2,[8][9][10][11][12][13]. Lowlevel laser therapy is one of the physiotherapy measures that can be taken for controlling neuropathic pain, and it has recently received much attention from researchers due to its low cost, being non-invasive and not having side effects [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy that aims to deliver a gene of interest to replace, inactivate or correct the defective gene to help the diseased tissue function properly is the most promising approach for curing these debilitating genetic diseases. Scientists have used multiple gene delivery techniques such as lipid mediated gene delivery ( 4 ), cationic polymers ( 5 ), electroporation ( 6 ), microinjection ( 7 ), and viruses ( 8 ). Due to their efficient mode of gene delivery, viruses such as lentivirus are popular vectors for gene delivery ( 9 ).…”
Section: Introductionmentioning
confidence: 99%